First case report of staghorn calculi successfully removed by mini‐endoscopic combined intrarenal surgery in a 2‐year‐old boy. (2nd July 2015) - Taguchi, Kazumi; Hamamoto, Shuzo; Okada, Atsushi; Mizuno, Kentaro; Tozawa, Keiichi; Hayashi, Yutaro; Kohri, Kenjiro; Yasui, Takahiro
Abstract Less‐invasive therapy for pediatric urolithiasis is available due to the miniaturization of equipment and improved optics; however, surgical treatment strategies, especially for large calculi, remain controversial. We describe here our experience of treating a 2‐year‐old boy with left renal staghorn calculi with a single session of mini‐endoscopic combined intrarenal surgery in the prone split‐leg position with pre‐ureteral stenting and the directional enhanced flow imaging ultrasound technique. This is the first report of successful pediatric mini‐endoscopic combined intrarenal surgery without any major complications. We believe this technique provides an important therapeutic option for large renal calculus in pediatric patients.